Pengaruh Organisasi Profesi Guru pada Pengembangan Profesionalisme Guru di Sekolah Menengah Pertama - Putri Permata Assiddiq Harahap; Siti Zahra Siagian; Victoria Grace Daely; Yeni Yolanda Simbolon; Yuli Indriani Lubis; Jamaludin Jamaludin (Universitas Palangka Raya, 2024)
This research aims to analyze the influence of professional teacher organizations on the development of teacher professionalism in junior high schools. Teachers as professionals need a platform to improve their competence and develop themselves on an ongoing basis. Teacher professional organizations play an important role in facilitating teacher professionalism development activities. This research uses a library method by collecting and reviewing various literature sources such as books, journals, research reports and scientific articles that are relevant to the research topic. The collected data was then analyzed qualitatively to determine the influence of professional teacher organizations on the development of teacher professionalism. The research results show that professional teacher organizations make a significant contribution in improving teachers' pedagogical, personal, social and professional competencies through various activities such as training, seminars, scientific discussion forums, as well as providing the latest learning resources and information.